Passivação do aço carbono em solução de poros de compósitos cimentícios com substituição de pó de vidro - Simões, Mariana Nuccitelli (Universidade Federal de São Carlos, 2024)
Society seeks solutions for sustainable concrete and mortar, with less use of natural resources and lower CO2 emissions. Therefore, the use of alternative materials to cement and/or natural aggregates comes to solve this problem. One of the issues studied is the incorporation of glass powder in partial cement replacements. As it is not a biodegradable material, the glass industry seeks to incorporate glass waste in the manufacture of new products, but is unable to process all the material available. Therefore, recycling glass in other industries, such as construction, is a good alternative for its reuse. The objective of the work was to evaluate the passivation of carbon steel bars immersed in pore solutions of cementitious composites produced with glass powder and/or silica fume. Cycles of non-destructive electrochemical tests were carried out, Open Circuit Potential (PCA), Electrochemical Impedance Spectroscopy (EIE) and Linear Polarization Resistance (LP) and, at the end, the potentiodynamic polarization test was carried out, in addition to the analyzes of Scanning Electron Microscopy (SEM) on steel bars. The pore solution was prepared from a mixture of materials (Portland cement, sand, silica fume, glass powder and water) using an electromagnetic stirrer. The solution was stirred for 3 hours and then filtered using a vacuum pump. From the electrochemical tests, it was shown that the bars immersed in the reference solution with silica obtained better performance in the formation of the passive film and that those immersed in the solutions with glass powder resulted in better film characteristics than in the reference solution. With SEM analyses, it was suggested that the solutions simulate the microstructure of cementitious compounds and that, after removing the solution and drying the bar, the bar did not undergo oxidation. Therefore, the use of glass destruction in cementitious composites is possible, focusing on the passivation of the steel inserted in them, enabling an environmental gain in the production of the material.
Passivation of carbon steel in cementious composite pore solution with glass powder replacement
Keywords: Compósitos cimentícios; Durabilidade; Passivação; Pó de vidro; Técnicas eletroquímicas; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL